Functional changes in the auditory cortex and associated regions caused by different acoustic stimuli in patients with presbycusis and tinnitus - Fuksa, Jakub; Profant, Oliver; Tintěra, Jaroslav; Svobodová, Veronika; Tóthová, Diana; Škoch, Antonin; Syka, Josef (Frontiers in Neuroscience, 2022)
Presbycusis and tinnitus are the two most common hearing related pathologies. Although both of these conditions presumably originate in the inner ear, there are several reports concerning their central components. Interestingly, the onset of presbycusis coincides with the highest occurrence of tinnitus. The aim of this study was to identify age, hearing loss, and tinnitus related functional changes, within the auditory system and its associated structures. Seventy-eight participants were selected for the study based on their age, hearing, and tinnitus, and they were divided into six groups: young controls (Y-NH-NT), subjects with mild presbycusis (O-NH-NT) or expressed presbycusis (O-HL-NT), young subjects with tinnitus (Y-NH-T), subjects with mild presbycusis and tinnitus (O-NH-T), and subjects with expressed presbycusis and tinnitus (O-HL-T). An MRI functional study was performed with a 3T MRI system, using an event related design (different types of acoustic and visual stimulations and their combinations). The amount of activation of the auditory cortices (ACs) was dependent on the complexity of the stimuli; higher complexity resulted in a larger area of the activated cortex. Auditory stimulation produced a slightly greater activation in the elderly, with a negative effect of hearing loss (lower activation). The congruent audiovisual stimulation led to an increased activity within the default mode network, whereas incongruent stimulation led to increased activation of the visual cortex. The presence of tinnitus increased activation of the AC, specifically in the aged population, with a slight prevalence in the left AC. The occurrence of tinnitus was accompanied by increased activity within the insula and hippocampus bilaterally. Overall, we can conclude that expressed presbycusis leads to a lower activation of the AC, compared to the elderly with normal hearing; aging itself leads to increased activity in the right AC. The complexity of acoustic stimuli plays a major role in the activation of the AC, its support by visual stimulation leads to minimal changes within the AC. Tinnitus causes changes in the activity of the limbic system, as well as in the auditory AC, where it is bound to the left hemisphere.